2012
DOI: 10.1186/1471-2326-12-6
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life in Middle Eastern children with beta-thalassemia

Abstract: BackgroundThalassemia is a common disorder worldwide with a predominant incidence in Mediterranean countries, North Africa, the Middle East, India, Central Asia, and Southeast Asia. Whilst substantial progress has been made towards the improvement of Health related quality of life (HRQoL) in western countries, scarce evidence-based data exists on HRQol of thalassemia children and adolescents living in developing countries.MethodsWe studied 60 thalassemia children from Middle Eastern countries with a median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
65
2
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 20 publications
(30 reference statements)
12
65
2
9
Order By: Relevance
“…Scores across all domains were higher in present study as compared to other studies (Ayoub et al 2013; Caocci et al 2012; Gharaibeh and Gharaibeh 2012; Wahyuni et al 2011; Surapolchai et al 2010; Clarke et al 2010; Ismail et al 2006). This may be attributed to the better access to health care facilities and better control of iron overload related complications at this tertiary care center.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Scores across all domains were higher in present study as compared to other studies (Ayoub et al 2013; Caocci et al 2012; Gharaibeh and Gharaibeh 2012; Wahyuni et al 2011; Surapolchai et al 2010; Clarke et al 2010; Ismail et al 2006). This may be attributed to the better access to health care facilities and better control of iron overload related complications at this tertiary care center.…”
Section: Discussioncontrasting
confidence: 56%
“…The lower scores in girls may be due to poor attention given to girl child in our society. On the contrary, some studies (Caocci et al 2012; Saha et al 2015) have reported better scores for girls and other studies have shown no difference between boys and girls (Thavorncharoensap et al 2010; Gharaibeh and Gharaibeh 2012; Torcharus and Pankaew 2011). …”
Section: Discussionmentioning
confidence: 97%
“…10 HRQoL is generally conceptualized as a multidimensional construct referring to patients' perceptions of the impact of disease and treatment on their physical, psychological, and social functioning and well-being. 11 Although some previous studies have investigated HRQoL issues in thalassemia patients receiving conventional treatment with blood transfusions and iron chelation, [12][13][14][15][16][17] there is a paucity of evidence-based data on HRQoL after HSCT. Moreover, previous reports in this area are limited by small sample size and a relatively short follow-up ranging from 1 to 6.5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Parents of the children with thalassemia major encounter various issues with taking care of their children. In order to provide the child and parents with proper cares, it is necessary to understand these problems (25,26).…”
Section: Introductionmentioning
confidence: 99%